Neuronal Alignment and Outgrowth on Microwrinkled Conducting Polymer Substrates. Issue 1795 (2015) - Bonisoli, Alberto; Marino, Attilio; Ciofani, Gianni; Greco, Francesco
ABSTRACT: We report on the results of culturing SH-SY5Y neuron-like cells on PEDOT:PSS wrinkled surfaces fabricated by thermally-induced shrinking of commercial polystyrene sheets. Such smart biointerfaces combine the functional properties of conducting polymers with the topographic patterning at the micro- and sub-microscale, as a result of surface wrinkling. By imposing mechanical constraints during shrinking, anisotropic topographic features are formed, with a spatial periodicity in the range 0.7 - 1.2 μm, tunable by varying the thickness of the PEDOT:PSS thin film. The effectiveness of wrinkled surfaces in enhancing and orientating the outgrowth of neurites is demonstrated by a 42% increase in length and by the 85% of neurites aligned along wrinkles direction (angle 0 < θ < 15°), after 5 days of differentiation. Furthermore, the conductive properties of the PEDOT:PSS film are retained after the surface wrinkling, opening the way for the exploitation of these smart biointerfaces for the electrical stimulation of cells.